Indonesian Multiculturalism and Nationalism in the Global Era: Its Relevance to History Education - Johan Setiawan (Swarnadwipa, 2024)
This article discusses Indonesian multiculturalism and nationalism in the global era. Various references indicate that today's society faces several problems, particularly related to the state of Indonesian multiculturalism and nationalism in the global era. Indonesia's multicultural status makes it unique and distinctive, but on the other hand, the pluralistic nature of society can give rise to conflict. Furthermore, the rapid development of science and technology has made it easier for people to communicate and interact with the world. Naturally, with easier access to information, Western culture will more easily enter Indonesia. This could lead to a shift in values, norms, and a love for Indonesian culture due to a lack of appreciation for indigenous Indonesian culture. The method used in writing this article is a descriptive qualitative research method with a literature review approach. The results obtained are: (1) To avoid conflict, preventative measures must be taken by strengthening intellectual capacity and morality, increasing self-confidence, strengthening communication skills, and fostering an appreciation for differences. (2) A process of infiltration is necessary to ensure that any culture entering Indonesia does not undermine the original cultural identity of the Indonesian people, which could lead to the erosion of Indonesian nationalism. These efforts are undertaken to revitalize the spirit of nationalism and maintain Indonesia's multicultural identity.